How schools affect neighbourhoods: a conceptual framework for the multiple roles of public schools - Oskar Rönnberg; Venla Bernelius; Isabel Ramos Lobato (Nordic Journal of Studies in Educational Policy)
Schools are often seen primarily as places of education and learning. However, in addition to providing pupils with knowledge and skills needed in life, schools have a central role in forming and structuring life in their neighbourhoods. In this paper, we propose a conceptual framework for understanding the role and potential of schools in neighbourhood and social development. We illustrate the conceptual framework with empirical data from a survey among residents in five Finnish cities, where the link between schools and neighbourhoods is traditionally strong as school admission is based on catchment areas. We argue for a broader perspective on schools by paying attention to the three significant roles of schools: their educational role, their role in structuring residential decisions and social composition of neighbourhoods, and thirdly, their role as a hub for services and social life.